2012
DOI: 10.1103/physrevlett.109.241802
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Higgs Boson at a Mass of 126 GeV on the Standard Model with Three and Four Fermion Generations

Abstract: We perform a comprehensive statistical analysis of the standard model (SM) with three and four generations using the latest Higgs search results from LHC and Tevatron, the electroweak precision observables measured at LEP and SLD, and the latest determinations of M(W), m(t), and α(s). For the three-generation case we analyze the tensions in the electroweak fit by removing individual observables from the fit and comparing their predicted values with the measured ones. In particular, we discuss the impact of the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
109
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(115 citation statements)
references
References 73 publications
(88 reference statements)
6
109
0
Order By: Relevance
“…lines have shown that the coefficients of the leading operators in this expansion can already be meaningfully constrained [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19].…”
Section: Jhep11(2013)111mentioning
confidence: 99%
“…lines have shown that the coefficients of the leading operators in this expansion can already be meaningfully constrained [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19].…”
Section: Jhep11(2013)111mentioning
confidence: 99%
“…However, since the observed Higgs candidate particle is produced at roughly the Standard Model rate, extensions of the Higgs sector beyond the Standard Model are extremely constrained. For example, a model with a sequential fourth generation of chiral fermions predicts large deviations in the Higgs rates [16][17][18][19][20] and is excluded by the limits on Higgs production for any Higgs mass below around 600 GeV [21,22]. The properties of these potential new colored particles are further limited by precision electroweak measurements.…”
Section: Introductionmentioning
confidence: 99%
“…We employ the one-loop contributions to the oblique parameters, assuming small mixing with the extra family, as in [8]. See [25] for some recent discussion of the more general case of potentially large mixing effects.…”
Section: A Methodsmentioning
confidence: 99%